Hubungan Stres dengan Motivasi Belajar pada Siswa SMA Negeri 1 Ubud - Kadek Berliantara; Putu Asih Primatanti; Ni Wayan Armerinayanti (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2024)
[The Relationship between Stress and Learning Motivation in Ubud 1 Public High School Students] Stress refers to mental and emotional disturbances that can arise from both internal and external factors. Learning motivation is a desire that oroginates within the student and lead to various learning activities. Due to the lack of previous research on this topic at SMA Negeri 1 Ubud, it is crucial to conduct this study in order to gather relevant , which could potentially benefit the school. This research can help the school prevent the factors that cause stress in students and increase the learning motivation. this study used descriptive analytic with a cross-sectional approach. This research was conducted at SMA Negeri 1 Data was collected using Perceived Stress Scale questionnaire (PSS-10) and Motivated Strategies for Learning Questionnaire (MSLQ-18). Furthermore, data analyzed both univariately and bivariately using the SPSS 25th version and Spearman test method, considering the analysis significant if the p value is less than 0.05. The univariate analysis revealed that the majority of students were 16 years old (36.2%), with a majority of female students (55.7%) and a majority of class XI students (33.8%). The Spearman correlation test's bivariate analysis yielded a significance value of 0.000, with a significant level of 0.05. The correlation coefficient, which stands at 0.241, indicates a weak relationship. The negative correlation coefficient number indicates an opposite relationship between the two variables, suggesting that higher stress levels lead to decreased learning motivation among SMA Negeri 1 Ubud students.